The Effect of Vitamin E-Coated Tracheotomy Cannula on Tracheal Reactive Oxygen Species - (:unkn) unknown (EKIN TIBBI YAYINCILIK LTD STI-EKIN MEDICAL PUBL, 2008)
Objectives: latrogenic airway injury after tracheotomy continues to be a serious clinical problem. Tracheotomy tubes can cause severe stomal stenosis in the trachea or infraglottic region. Vitamin E is a scavenger of different free radicals by working as an antioxidant. The aim of the present study was to evaluate the effect of vitamin E-coated tracheotomy tube insertion on the quantity of free radicals in rat tracheal tissue. Materials and Methods: Male Sprague-Dawley rats were divided into three groups of six animals each. Ordinary tracheotomy tubes were applied to the first group and vitamin E-coated tracheotomy tubes were applied to the second group. The third group was used as control. Animals were killed and chemiluminescence measurements were made for tracheal tissue. Results: Reactive oxygen species (ROS) levels were significantly increased in the first group of rats compared to those in control animals. ROS levels were statistically significantly decreased in the second group as compared to the first group. Conclusion: Our results indicate that vitamin E decreases tracheotomy-induced ROS levels in tracheal tissue.
Keywords: Tracheotomy; free oxygen radicals; vitamin E; LARYNGOTRACHEAL STENOSIS; FREE-RADICALS; CANINE MODEL